5(y+3)-4(1-5y)=-39

Simple and best practice solution for 5(y+3)-4(1-5y)=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+3)-4(1-5y)=-39 equation:


Simplifying
5(y + 3) + -4(1 + -5y) = -39

Reorder the terms:
5(3 + y) + -4(1 + -5y) = -39
(3 * 5 + y * 5) + -4(1 + -5y) = -39
(15 + 5y) + -4(1 + -5y) = -39
15 + 5y + (1 * -4 + -5y * -4) = -39
15 + 5y + (-4 + 20y) = -39

Reorder the terms:
15 + -4 + 5y + 20y = -39

Combine like terms: 15 + -4 = 11
11 + 5y + 20y = -39

Combine like terms: 5y + 20y = 25y
11 + 25y = -39

Solving
11 + 25y = -39

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 25y = -39 + -11

Combine like terms: 11 + -11 = 0
0 + 25y = -39 + -11
25y = -39 + -11

Combine like terms: -39 + -11 = -50
25y = -50

Divide each side by '25'.
y = -2

Simplifying
y = -2

See similar equations:

| 17=8x+1-4x | | 4y-4x^3=0 | | 18/-3=6 | | y=x^2+6x+14 | | 4x^2+16x-12y-44=0 | | 51=-3(m+7)+m | | x^2-33x+100=56-9x | | 6x+120=128 | | -18/-3=-6 | | -3(4p+5)-2(5-14p)=3(6+5p) | | 12=5x-7y | | 3xy+12x^2-4yx-10x+7xy-9x^2= | | D+1.0=9.2whatisD | | 9+18=-3(3x-9) | | 0.9x-0.5=6 | | x^2-33x+100=9x+y-56 | | 6x+8=5x+6 | | 9x^2-96x+192=0 | | 3(x+12)-16=8x | | x^2-33+100=9x+y-56 | | 4(3-2x)=3-5x | | 2x+20+60= | | 10y+5(-1)=-5 | | 6(y+4)=78 | | x^2-2xy+y^2=34225 | | (7y+8)-(7+6y)=11 | | 11-3x=19+2x | | (2x+20)+60= | | 6(a-5)-5a= | | 5x+4(1)=24 | | 7(z-3)=6z | | 2x-6=8x+14 |

Equations solver categories